THE ROLE OF STRATEGIC MANAGEMENT OF LEADERS IN MANAGING ISLAMIC EDUCATIONAL INSTITUTIONS - Dantika, Fina Azizah; Nugraha, Mulyawan Safwandy (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2024)
Abstract: An ideal leader is someone whose life and personality can inspire others to emulate. A good leader is authoritative, has a righteous way of life, and is worthy of being a role model. This is not due to their power, prestige, personality, or specific status. On the other hand, most "leadership" in the world today is merely ergonomic, based on the threat of punishment and the promise of reward. The progress of an organization largely depends on its governance and management system. This means that through proactive leadership management, we can produce high-quality human resources. Data collection methods used include interviews, documentation, and observation. Data processing techniques include reduction, data presentation, and drawing conclusions. The validity of the data is ensured by credible and confirmable techniques. The research results show that the role of leadership at MIN Bandung is greatly felt by all educators and educational staff. The leader provides guidance to subordinates, is responsible for implementation, and serves as a highly exemplary figure. Keywords: Management, Strategic, Leader